If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-1) = y + 3 Multiply 2 * -1 -2 = y + 3 Reorder the terms: -2 = 3 + y Solving -2 = 3 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -2 + -1y = 3 + y + -1y Combine like terms: y + -1y = 0 -2 + -1y = 3 + 0 -2 + -1y = 3 Add '2' to each side of the equation. -2 + 2 + -1y = 3 + 2 Combine like terms: -2 + 2 = 0 0 + -1y = 3 + 2 -1y = 3 + 2 Combine like terms: 3 + 2 = 5 -1y = 5 Divide each side by '-1'. y = -5 Simplifying y = -5
| 3(w+2)+2(w-3)+5=25 | | 8(5x-1)=132 | | x+2-(4-x)=16 | | 1/4(16+4p) | | y=-1/2x+7 | | (y)+30=3y | | 2x+6=-5/x | | 2-(4-3-2/2) | | 10-(6+7x)=-17 | | y=7/5x-4 | | 2x-(x+7)=0 | | 6x^2+432=0 | | 5x^3-x^4=X^3 | | 7e+11=-17 | | 4x/8=16 | | x/6=7/18 | | 7.32a=13.36+2.81a | | y=-8/3x-5 | | 4(b+3)-2b=26 | | 4x+9a+7a=17 | | 30000=.06x+.09(30000-x) | | 5=7/6x | | 3(a+2)-2a=14 | | 207=11.5x*132.25 | | 21x^3y+3xy^3-6xy=0 | | 2.5(6+k)=3k | | 8.5m=-34 | | Y=10x+b | | 8x-3+5x=23 | | 7(d+3)=-18+4 | | y-(4-x-y/2) | | 5(x-12)=3x |